The Customer Relationship Management In Terms of Business Practice In India: Creating Competitive Advantage through Customer Relationship Management (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Today’sbusinesses compete with multi-product offerings created and delivered bynetworks, alliances and partnerships of many kinds. Both retaining customersand building relationships with other value-adding allies is critical tocorporate performance. The adoption of C.R.M. is being fuelled by recognitionthat long-term relationships with customers are one of the most importantassets of an organization. The focus of CRM is on creating value for thecustomer and the company over the longer term. When customers value thecustomer service that they receive from suppliers, they are less likely to lookto alternative suppliers for their needs .CRM enables organizations to gain‘competitive advantage’ over competitors that supply similar products orservices.